A proteomic glimpse into the initial global epigenetic changes during HIV infection. Issue 19 (5th September 2014) - Britton, Laura‐Mae P.; Sova, Pavel; Belisle, Sarah; Liu, Shichong; Chan, Eric Y.; Katze, Michael G.; Garcia, Benjamin A.; Vondriska, Thoms M.; Jensen, Ole N.
<x xml:space="preserve">Abstract</x> HIV‐1 replication requires the insertion of viral DNA into the host genome, which is catalyzed by HIV‐1 integrase. This integration event can lead to vast changes in the chromatin landscape and gene transcription. In this study, we sought to correlate the extensive changes of histone PTM abundances with the equally dynamic shifts in host transcriptional activity. To fully capture the changes that were occurring during the course of HIV‐infection, we performed time‐courses in which we extracted both histones and mRNA from HIV‐infected, UV‐inactivated HIV‐infected and mock‐infected SUP‐T1 cells. We then analyzed the alterations to histone PTM profiles using nano‐LC‐MS/MS, as well as the expression of chromatin‐associated enzymes, such as histone deacetylases, acetyltransferases, demethylases, methyltransferases, and histone chaperone proteins. As expected, we observed major changes in histone PTM abundances, which we linked to massive fluctuations in mRNA expression of associated chromatin enzymes. However, we find few differences between HIV and HIVUV (UV‐inactivated) infection, which suggests that initial histone PTM changes during HIV infection are from the host in response to the infection, and not due to the HIV virus manipulating the transcriptional machinery. We believe that these preliminary experiments can provide a basis for future forays into targeted manipulations of histone PTM‐regulated aspects of HIV progression through its replication cycle.